Letting Out the Secret - Violence in Lesbian Relationships - Lockhart, Lettie L.; White, Barbara W.; Causby, Vicky; Isaac, Alicia (Journal of interpersonal violence, 1994)
Over the past 2 decades, a variety of studies on domestic violence has confirmed that abuse is widespread. This increased attention to violence in intimate relationships has been focused on heterosexual couples, despite the assertion that 4-10% of the population is homosexual. Violence among lesbian couples has largely been ignored by family violence researchers, but clinical practitioners who are sought out by the battered and/or the batterers for therapy are well aware of the extent and nature of the battering that takes place in these relationships, and that battering is not limited to heterosexual relationships. This exploratory study takes a step toward an understanding of lesbian violence by examining the incidence, forms, and correlates of violence in lesbian relationships. Based upon the responses of 284 lesbians to a questionnaire, it was found that lesbian violence is not a rare phenomenon. This finding reflects the need for further research into this social problem in all intimate relationships, including homosexual relationships